Удосконалення резонансного діелькометричного методу контролю та визначення вологості рідких неполярних діелектриків - Коробко, Олександр Анатолійович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Дисертація на здобуття наукового ступеня кандидата технічних наук (доктора філософії) за спеціальністю 05.11.13 "Прилади і методи контролю та визначення складу речовин" (15 – Автоматизація та приладобудування) – Національний технічний університет "Харківський політехнічний інститут". Мета роботи: удосконалення резонансного діелькометричного методу контролю та визначення вологості рідких неполярних діелектриків задля підвищення його чутливості до рівня 10⁻⁵ з одночасною мінімізацією впливу "сортової невизначеності". Запропоновані та досліджені: спрощена математична модель емульсії на основі моделі штучного діелектрика Кока; нові багаточастотні різновиди резонансного діелькометричного методу; новий тип розподіленого вимірювального перетворювача. Розроблено, теоретично та експериментально досліджено вологоміри середньочастотного та дуже високочастотного діапазонів. Експериментальним шляхом підтверджено досягнення мети роботи.

Thesis for a candidate degree (PhD) in specialty 05.11.13 "Instruments and methods of control and determination of substances" (15 – Automation and Instrumentation) − National Technical University "Kharkiv Polytechnic Institute". The thesis is devoted to the improvement of the resonant dielectric method of monitoring and determining the humidity of emulsions such as liquid non-polar dielectric - water in order to increase its sensitivity to level 10⁻⁵ while simultaneously minimizing the type and grade of non-polar dielectric ("varietal uncertainty") on the measurement results. An analytical review and analysis of the existing methods and means of implementation of the dielectric method in general and its resonant variety has been carried out. The main research areas have been identified: development of a simplified emulsion model; development of new varieties of the resonant dielectric method with minimization of the effect of "varietal uncertainty" for measuring humidity at a level of 10⁻⁵; development of a new type of distributed transducer. A simplified emulsion model was chosen based on the Kok artificial dielectric model, its applications were determined by frequency, humidity, and the values of its systematic errors were determined. New multifrequency varieties of the resonant dielectric method have been developed based on the proposed mathematical model of the emulsion, taking into account the parasitic capacitances of the measuring generator and the measuring converter. Metrological characteristics of the generalized four-frequency method and its simplified three-and two-frequency varieties are obtained. The areas of applicability of multifrequency methods are analyzed and their systematic errors are determined. The most sensitive method, the two-frequency method, was determined, the effect of dielectric losses in water was analyzed for it, and the generation frequency of the measuring generator, which corresponds to its maximum sensitivity, 100 MHz, was determined. A new type of distributed-type measuring transducer is proposed for the practical implementation of the two-frequency method — a stepwise heterogeneous coaxial resonator; its theoretical and experimental studies are carried out; its advantages in relation to the known transducers are determined. A hygrometer of the mid-frequency range based on a concentrated-type capacitive transducer and a hydrometer of a very high-frequency range based on a stepped heterogeneous coaxial resonator have been developed. The circuit solutions of the measuring transducer and the measuring generator of the hygrometer of the midfrequency range, which provided the minimum values of their parasitic capacitances, were developed and implemented. The circuit solutions of the measuring transducer and the measuring generator of a hygrometer of a very high frequency range have been developed and implemented, which provided almost zero effect of their parasitic capacitances. A methodology has been developed for conducting experimental research on the implementation of four- and three-frequency methods using a mid-range moisture meter and implementing a two-frequency method and a simplified version of it using a very high-frequency moisture meter. Experimental studies on manufactured test emulsions, as well as analysis and processing of their results, were carried out. For all developed multi-frequency methods and moisture values of test emulsions in the range of 10⁻⁴ – 10⁻², the value of the relative extended uncertainty of moisture measurement did not exceed 5.28 %. For the humidity of the test emulsion 10⁻⁵, the value of this uncertainty did not exceed 10.39 % (due to the lack of stability of the frequency of the reference generator frequency Ch 3 - 34, which was used in the research). The developed improved multi-frequency resonance dielectric methods for determining humidity have increased the sensitivity to a level of 10⁻⁵ while minimizing "varietal uncertainty".
Improvement of resonance dielcometrics method of control and determination of moisture content liquid nonpolar dielectrics
Keywords: емульсія; неполярний рідкий діелектрик; вологість; резонансний діелькометричний метод; сортова невизначеность; ємнісний вимірювальний перетворювач; вимірювальний генератор; ступінчастий неоднорідний коаксіальний резонатор; автореферат дисертації; emulsion; non-polar liquid dielectric; humidity; varietal uncertainty; resonant dielectric method; capacitive measuring transducer; measuring generator; stepped non-uniform coaxial resonator; 621.317.39